Human myeloid dendritic cells treated with supernatants of rotavirus infected Caco-2 cells induce a poor Th1 response (2012)
We have previously shown that human myeloid dendritic cells treated with purified rotavirus induce an allogenic Th1 response. To determine if rotavirus in the context of an intestinal microenvironment modulates the function of dendritic cells, we treated these cells with supernatants from non-infected or infected Caco-2 cells and studied their capacity to promote Th1 or Th2 responses. Dendritic cells treated with supernatants from rotavirus-infected Caco-2 cells promoted a significantly lower Th1 response, in comparison with those treated with purified rotavirus. We wanted to establish if TGF-?1, induced, or TSLP, not induced, during rotavirus infection, could mediate this effect. Neutralization of TGF-? but not TSLP in the supernatant prior to treatment of dendritic cells increased their capacity to promote a Th1 response. The results suggest that the TGF-?1 induced by rotavirus could be an immune evasion mechanism, and may partially explain the poor rotavirus-specific T cell response we have previously evidenced. © 2011 Elsevier Inc.